Diagnostic Value Of Qtc Dispersion And And Qt Dispersion Ratio Changes On Stress Test In Detecting Significance Of Coroner Lesion In Stable Angina Pectoris Patients - putri yeantesa; Hauda El Rasyid; Masrul Syafri; Ricvan Dana Nindrea (Jurnal Kardiologi Indonesia, 2019)
Background : Treadmill exercise test remains an important method and often used in the initial evaluation of patients with chest pain and can be a filter for more expensive invasive diagnostic. Increased QT dispersion (QTD) occurs because of the heterogeneity of ventricular repolarization because transient ischaemia during a treadmill stress test can be a marker of coronary artery disease (CAD) and can improve the accuracy of exercise tests to diagnose CAD, but this parameter is still controversial. Method : This is an analytic observational approach with a cross sectional study. Data was taken retrospectively at the Heart Center Installation at RSUP Dr. M. Djamil Padang, from March to April 2019, stable angina pectoris patient with a positive treadmill stress test who underwent coronary angiography as the subject. Bivariate analysis was performed on changes in QTcD (∆QTcD) and QTdR (∆QTdR) variables on the significance of coronary lesions by the chi-square method, after which a diagnostic test was based on receiver operating curve (ROC) analysis. Study Result : There were 122 subjects and found that older age, male and smoking were more common in groups with significant coronary lesions. Cut off point for ∆QTcD is ≥13 ms with a sensitivity of 87,1% and specificity 85,2% and AUC 95,1%, while ∆QTdR ≥5.5% with sensitivity 85,7% and specificity 81,9% and AUC 90,5% are related to significancy of coronary lesion. Obtained subjects with significant lesions generally had a value of ∆QTcD ≥ 13 ms (p <0.001) and ∆QTdR ≥ 5.5% (p <0.001). Conclusion : The use of ∆QTdR dan ∆QTdR parameters as ECG variables, which are easily obtained in evaluating stress tests, can improve the diagnostic accuracy of exercise tests. In addition, evaluation of ∆QTdR dan ∆QTdR can provide information about the incidence of CAD. Keywords : ∆QTcD, ∆QTdR, Treadmill Exercise Test, Coronary Lession Significancy